Evolution of milk production systems in tropical Latin America and its interrelationship with markets: an analysis of the Colombian case - Holmann, Federico J.; Rivas Ríos, Libardo; Carulla, J.; Rivera, B.; Giraldo, L.; Guzmán, S.; Martínez, M.; Medina, A.; Farrow, Andrew (2003)
The objectives were to: (1) identify and quantify the effect of technological change on productivity, profitability, and competitiveness in different milk production systems and regions of the country; (2) analyze the relationship between productivity, technological change, profitability, and competitiveness; (3) analyze the evolution of milk production systems in Colombia; and (4) discuss the market concentration and its impact on the formation of milk price. Data came from a survey to 545 farms during the year 2000 in five regions: Caribbean and Piedmont in the lowlands, Coffee Growing, Antioquia, and the Cundiboyacense altiplanicie in the highlands. The survey was designed to quantify inputs and products in order to determine costs and prices at the farm level in order to calculate (a) variable costs for feed supplementation, labor, health, reproduction, fertilization, and irrigation; (b) gross income from the sale of milk and beef, and (c) to characterize farms according to productivity level and management practices. The statistical analysis of multiple correspondence and general linear models were used to explain the variability observed between productivity and profitability as a function of technological change. Independent of the production system or the region where farms were located, the increase in competitiveness was in direct relationship with herd size. Thus, as herd size increased, production costs per unit of milk and beef decreased, net incomes per cow increased, and the return to capital investment improved. However, when this increase in competitiveness was associated with increases in productivity, this trend was not observed, which suggested that highly productive farms were not necessarily competitive. The dual-purpose system was the most profitable one in the Piedmont, Caribbean, and Coffee growing regions while in Antioquia and in the Cundiboyacense altiplanicie the most profitable was the specialized dairy system. With regards to technological change, the adoption of improved pastures and the investment in pasture divisions for a more efficient rotation generated higher productivity and income in all regions and production systems, as well as increased competitiveness through a reduction in production costs per unit of milk and beef. The use of strategic feed supplementation to the basal diet of forage had mixed effects. The best economic response to this supplementation in lowland regions (i.e., Piedmont and Caribbean) was with low quantities (i.e., < 0.5 kg DM/cow/day) of feed supplements while in highland regions (i.e., Coffee Growing area, Antioquia and the Cundiboyacense altiplanicie) was with moderate quantities (i.e., between 0.5 and 2 kg DM/cow/day). The use of fertilization and irrigation increased productivity, but reduced net income and increased production costs, except in the Cundiboyacense altiplanicie. The practice of milking twice a day increased both productivity and profitability and reduced production costs, except in the Caribbeanregion. Farms that de-wormed milking cows with low frequency against internal and external parasites obtained higher incomes and lower production costs in comparison with farms that de-wormed cows with higher frequency although there were no differences in productivity. The amount of years of experience of farmers at producing milk was a key factor to increase profits, although not productivity. Farms located in sites where the commercial value of land was high (>US$6,000/ha) and near market centers had higher productivity that those with commercial value of land medium ($3,000 to $6,000/ha) and low (<$3,000/ha) but were less profitable in all regions.